2022
DOI: 10.1001/jama.2022.7393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Robot-Assisted Radical Cystectomy With Intracorporeal Urinary Diversion vs Open Radical Cystectomy on 90-Day Morbidity and Mortality Among Patients With Bladder Cancer

Abstract: This is a repository copy of Effect of robot-assisted radical cystectomy with intracorporeal urinary diversion vs open radical cystectomy on 90-day morbidity and mortality among patients with bladder cancer : a randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 38 publications
3
71
1
1
Order By: Relevance
“…Similarly, robotic-assisted adrenalectomy (RAA) is safe and effective for benign adrenal masses, with a wide operative time of 98–234 min, a hospital stay of 1.1–6.4 days, estimated blood loss of 50–576 mL, and laparoscopic or open conversion rates of 0 = 40%. [ 30 32 ] Brunaud and associates reported that RAA was two times more costly than the laparoscopic approach, with a 10% perioperative complication rate,[ 33 ] while Giulianotti et al . reported a 2.4% postoperative complication rate and 2.4% mortality rate.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Similarly, robotic-assisted adrenalectomy (RAA) is safe and effective for benign adrenal masses, with a wide operative time of 98–234 min, a hospital stay of 1.1–6.4 days, estimated blood loss of 50–576 mL, and laparoscopic or open conversion rates of 0 = 40%. [ 30 32 ] Brunaud and associates reported that RAA was two times more costly than the laparoscopic approach, with a 10% perioperative complication rate,[ 33 ] while Giulianotti et al . reported a 2.4% postoperative complication rate and 2.4% mortality rate.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The primary outcome of the iROC trial was that patients treated with intracorporeal RARC had a higher number of days out of hospital within 90 days (82 days v 80 days). Secondary findings suggested a lower risk of thromboembolic complications (2% v 8%) and lower wound complications (6% v 16%) in the RARC treated patients 24 . Patients treated with ORC had poorer quality of life and greater disability at 5 weeks, which was subsequently not significantly different beyond 12 weeks 24 .…”
mentioning
confidence: 92%
“…This led to the development of the iROC trial, a multicentre RCT comparing ORC with intracorporeal RARC. This phase 3 trial used a novel primary endpoint of number of days alive and out of hospital within 90 days from surgery, 23 and has recently reported outcomes 24 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Few multi-institutional randomized controlled trials were able to evaluate the impact of robotics in complex oncologic procedures and have shown excellent perioperative and quality-of-life outcomes. 1,2 We agree that the assessment of robotics in radical nephrectomy with IVC thrombectomy using a randomized controlled trial might be challenging, and hence a well-structured multi-institutional registry with collaborative reporting could be a feasible alternative.…”
mentioning
confidence: 99%